Bursa City Museum From Past To The Present - Silav, Muna (The Turkish Online Journal of Design Art and Communication, 2011)
Museums are places that transfers social, economic and cultural heritage from past to present. Society’ lifestyle, traditions, and habits are memory of the city. Regarded as exhibiting the cultural values of the past and the city's memory, the museums carry the characteristics values of society and value judgments. Playing an important role in the formation of Turkish culture and keeping it alive the city of Bursa has protected its historic heritage until the present day. This city, which was capital of the Ottoman Empire for many years, is one of the centers of rich culture and civilization. With a reputation, especially as a center of sericulture and weaving, Bursa is also has a unique historical heritage along with its inns, spas, shrines, public baths and fountains and many original structure belong to Republican period. Bursa City Museum is an institution that exhibits documenting the social development of the city throughout history. The purpose of this study is to evaluate the place and content of Bursa City Museum, which is open to the public, in society.
Keywords: Museum; Müze; City Museum; Şehir Müzesi; Bursa City Museum; Bursa Şehir Müzesi